2010
DOI: 10.1002/asna.200911297
|View full text |Cite
|
Sign up to set email alerts
|

Orbital eccentricity of the symbiotic star MWC 560

Abstract: We present projected rotational velocity measurements of the red giant in the symbiotic star MWC 560, using the highresolution spectroscopic observations with the FEROS spectrograph. We find that the projected rotational velocity of the red giant is v sin i= 8.2 ± 1.5 km s −1 , and estimate its rotational period to be Prot = 144 -306 days. Using the theoretical predictions of tidal interaction and pseudosynchronization, we estimate the orbital eccentricity e = 0.68−0.82. We briefly discuss the connection of ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The modulation at the binary period P2 is primarily due to the eccentricity of the binary orbit. Zamanov et al (2010) We now suggest that the P3=722 d is the sidereal rotation period of the giant. The second The period P4=1150 d satisfies P4=1/(1/P3-1/P2) (See Table 3), i.e.…”
Section: Qualitative Modelmentioning
confidence: 77%
See 1 more Smart Citation
“…The modulation at the binary period P2 is primarily due to the eccentricity of the binary orbit. Zamanov et al (2010) We now suggest that the P3=722 d is the sidereal rotation period of the giant. The second The period P4=1150 d satisfies P4=1/(1/P3-1/P2) (See Table 3), i.e.…”
Section: Qualitative Modelmentioning
confidence: 77%
“…The modulation at the binary period P2 is primarily due to the eccentricity of the binary orbit. Zamanov et al (2010) estimated it to be as high as 0.68. Close to periastron passages of the system, the L1 point of its equi-potential Roche lobes is getting closer to the giant center, exposing deeper layers of the giant atmosphere to the gravitational pool of the companion.…”
Section: Qualitative Modelmentioning
confidence: 99%
“…Using high-resolution spectroscopic observations and the cross-correlation function method, Zamanov et al (2007) find a typical rotational velocity of the K and M giants in S-type symbiotic stars to be 4.5 < v rot sin(i) < 11.7 km s −1 . These results were confirmed by Zamanov & Stoyanov (2012). Using new data for 55 field M0 III -M6 III giants, they indicated a mean v rot sin(i) = 5.0 km s −1 and median v rot sin(i) = 4.3 km s −1 .…”
Section: Parameters Of the Rg Windmentioning
confidence: 52%
“…Another possibility how to compress the wind from a star to the equatorial plane is the rotation of the central star (Bjorkman and Cassinelli , 1993). Zamanov and Stoyanov (2012) found that giants in symbiotic stars rotate with a mean v sin(i) ∼ 8 km s −1 . Using this value and other characteristic parameters of the giant's wind in symbiotic stars (e.g.Ṁ giant,wind ∼ 10 −7 M ⊙ yr −1 as above and terminal velocity of 20-40 km s −1 ), the wind compression at the orbital plane and a distance of 2-3 A.U.…”
Section: On the Accretion Mechanismmentioning
confidence: 99%